(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Locations of species listed in the Red Book of the Kyrgyz Republic and conservation of especially valuable trees and shrubs: Fumariola turkestanica Korsh., Malus sieversii (Ledeb.) M. Roem.., Lonicera paradoxa Pojark. Amygdalis bucharica Korsh., Juniperus seravschanica Kom., J. semiglobosa Regel, Juglans regia L , Pistacia vera L.